THE ENTITY APPROACH TO CONSOLIDATED STATEMENTS. - Moonitz, Maurice (The Accounting Review, 1942)
This article presents information on entity approach to consolidated statements. The central premise is that consolidated statements are exhibits in conventional accounting form of the status and the operations of a group of related companies. The substitution of the concept of economic entity for that of legal entity raises the problem of the scope of the consolidation. In principle the solution of the problem, is dear, namely, include all those companies whose policies are controlled by a dominant parent corporation. The entity concept requires the presentation of assets and liabilities at figures consistent with the viewpoint of a single operating unit. The stockholders of the parent company acting through a board of directors to whom power of administration is delegated constitute the controlling or dominant interest. Consequently, assets must be listed in terms of their relation to the dominant interest. Consolidated statements are not prepared for the purpose of informing minority interests of the status of their investments. For this information, minority interests must refer to the statements of the company in which they have an equity.